Legal Regulation of the Principles of State Activity in Family Relations - Nalyvaiko, Larysa; Obushenko, Nataliia; Boikov, Vladyslav; Hryshyna, Natalia; Makhova , Liliia (Jurnal Cita Hukum, 2025)
This work examines some challenges in the application of the principles of family law. It is found that the principles of family law cannot replace the legal norms that regulate family relations. However, the regulatory influence of family law norms is determined and limited by its principles. It is proven that the principles of family law can be applied by authorized law-making bodies (in the process of law-making), administrative, judicial bodies, and subjects of family relations (in the process of law enforcement). It is established that the legality of the actions of public institutions and private individuals directly depends on compliance with the principles of family law. It is substantiated that the principles of family law are implemented in the process of law-making, implemented through the norms of law, and in the process of direct application. In the process of law-making, the principles of family law establish requirements for law-making activity that cannot contradict general values. They determine the content of legal norms that must reflect these values and serve as a criterion for the conformity of family law norms with the law. It has been established that the application of family law principles is possible by embedding them in family law norms. At the same time, the principles of family law are not limited to the list that can be fixed in written law. It has been proven that consolidating family law principles in written law contributes to their practical implementation. The features of applying family law principles through legal analogy have been studied. It has been established that the analogy guarantees participants in family relations that their rights and obligations will be regulated, allowing them to resolve cases within the framework of family legislation or based on the principles of family law. REFERENCES: Decision of the Tyachiv District Court of the Transcarpathian region dated May 15, 2019, in case No. 307/1041/19. http://www.reyestr.court.gov.ua/Review/81775605 General theory of law: textbook / ed. by M.I. Kozyubry. Kyiv, 2015. 392 p. Halaburda, Nadiia. Leheza, Yevhen, Chalavan, Viktor. Yefimov, Volodymyr. Yefimova, Inna. 2021. Compliance with the principle of the rule of law guarantees the legality of providing public services in Ukraine. Journal of law and political sciences. Vol. 29, Іssue 4, 100–121. Kobrusieva, Yevheniiа. Leheza, Yevhen. Rudoi, Kateryna. Shamara, Oleksandr. Chalavan, Viktor. 2021. International standards of social protection of internally displaced persons: administrative and criminal aspects. Journal Cita Hukum Indonesian Law Journal. Vol. 9, No. 3, 461–484. DOI: https://doi.org/10.15408/jch.v9i3.23752 Kostruba A.V. Analogy of law and law as a factual fiction and a way to "rehabilitate" the mechanism of termination of rights. Journal of the Kyiv University of Law. 2012. No. 3. P. 185–189. Kroitor V.A. Eliminating gaps in civil law using analogy of law, analogy of law, and inter-branch analogy. Forum of Law. 2016. No. 3. P. 159–166. Kulinich, Olha. Leheza, Yevhen. Zadyraka, Nataliia. Taranenko, Kseniia, Kostiuk, Tetiana. 2023. Electronic Judicial Procedure as an Element of Access to Justice Regarding Protection of Rights of Individuals: Legal, Administrative, Theoretical, and Informational Aspects. Journal Cita Hukum Indonesian Law Journal. 11 (3), 443–456. DOI: https://doi.org/10.15408/jch.v11i3.36298 Leheza, Y., Kolomoiets, Y., Chalyk, V., Kovalchuk, Y., & Sakhno, A. (2024). Foreign experience of financial-legal and administrative-legal regulation of the activities of public administration bodies. Revista do Curso de Direito do UNIFOR, 15(1), 51–60. DOI: https://doi.org/10.24862/rcdu.v15i1.1832 Leheza, Y., Korniienko, M., Berezniak, V., Мariienko, А., & Radchuk, A. (2024). Legal Regulation of Liability for Illegal Deportation of Children: Administrative, Criminal Aspects, Experience of Ukraine and International Standards. Revista Jurídica Portuguesa, 257–274. https://doi.org/10.34625/issn.2183-2705(36)2024.ic-11 Leheza, Y., Shcherbyna, B. Leheza, Yulia. Pushkina, Olena & Marchenko O. (2023). “Features of Applying the Right to Suspension or Complete/ Partial Refusal to Fulfill a Duty in Case of Non-Fulfilment of the Counter Duty by the Other Party According to the Civil Legislation of Ukraine.” Revista Jurídica Portuguesa, 340–359. Retrieved from https://revistas.rcaap.pt/juridica/article/view/29662 Leheza, Yevhen. Filipenko, Tatiana. Sokolenko, Olha. Darahan, Valerii, Kucherenko, Oleksii. 2020. Ensuring human rights in Ukraine: problematic issues and ways of their solution in the social and legal sphere. Cuestiones políticas. Vol. 37 n.º 64 (enero-junio 2020). P. 123–136. DOI: https://doi.org/10.46398/cuestpol.3764.10 Leheza, Yevhen. Pisotska, Karina. Dubenko, Oleksandr. Dakhno, Oleksandr. Sotskyi, Artur. “The essence of the principles of Ukrainian law in modern jurisprudence”. Revista jurídica portucalense, December (2022): 342–363. https://doi.org/10.34625/issn.2183-2705(32)2022.ic-15 Leheza, Y. Shcherbyna, Bogdan. Leheza, Yulia. Pushkina, Olena. Marchenko, Olesia. (2024). Características de la suspensión o de la denegación total o parcial del cumplimiento de una obligación en caso de incumplimiento de la contraparte, según la legislación civil ucraniana. Novum Jus, 18(2), 131–150. https://doi.org/10.14718/NovumJus.2024.18.2.5 Leheza, Y. Yerofieienko, Larysa. Komashko, Volodymyr. (2023). Propiedad intelectual en Ucrania bajo la ley marcial: regulación jurídica, aspectos administrativos y civiles. DIXI, 26(1), 1–11. https://doi.org/10.16925/2357-5891.2024.01.09 URL. https://revistas.ucc.edu.co/index.php/di/article/view/4960 Leheza, Yevhen. Yurovskа, Viktoriia. Zamryha, Artur. Ulozhenko, Vadym, Bohdan. Bohdana 2024. Administrative and legal regulation of the status of internally displaced persons in Ukraine during the war. University of Western Australia Law Review. 51 (2). 297–313. https://www.uwa.edu.au/schools/-/media/documents/uwa-law-review/volume-51-issue-2/leheza-et-al-formatted.pdf Matviichuk, Anatolii. Shcherbak, Viktor. Sirko, Viktoria. Malieieva, Hanna. Leheza, Yevhen. 2022. Human principles of law as a universal normative framework: Principios humanos del derecho como marco normativo universal. Cuestiones Políticas, 40(75), 221–231. https://doi.org/10.46398/cuestpol.4075.14 Nalyvaiko, L., Hryhorchuk, M, Shevchenko, A, Melnyk, M, & Dolhoruchenko, K. (2023). Protection of Property Rights during the Russian-Ukrainian War: Theoretical and Legal Analysis. Access to Justice in Eastern Europe, 2(19), 172–190. URL: https://ajee-journal.com/protection-of-property-rights-during-the-russian-ukrainian-war-theoretical-and-legal-analysis. DOI: https://doi.org/10.33327/AJEE-18-6.2-n000206 Nalyvaiko, L., Pryputen, D., Verba, I., Lebedieva, Yu., & Chepik-Trehubenko, O. (2023). The European Convention on human rights and the practice of the ECTHR in the field of gestational surrogacy. Access to Justice in Eastern Europe, 2(19), 206–219. URL: https://ajee-journal.com/upload/attaches/att_1684147648.pdf. DOI: https://doi.org/ 10.33327/AJEE-18-6.2-n000203 Nalyvaiko, L., Маrсhenko, O., & Іlkov, V. (2018). Conceptualisation of the Phenomenon of Corruption: International Practices and Ukrainian Experience. Economic Annals-XXI, 172(7-8), 32-37. URL: https://ea21journal.world/index.php/ea-v172-06/ DOI: https://doi.org/10.21003/ea.V172-06 Nalyvaiko, Larysa Leheza, Yevhen, Sachko, Oleksandr. Shcherbyna, Victor. Chepik-Trehubenko. Olha. 2022. Principles of law: Methodological approaches to understanding in the context of modern globalization transformations. Ius Humani. Law Journal, 11(2), 55–79. https://doi.org/https://doi.org/10.31207/ih.v11i2.312 Osadchuk S.S. Application of the principles of law in law-making and law-enforcement processes. Our law. 2012. No. 3. Part 3. P. 32–37. Pidvalna M.Z. Problems of applying the principle of the rule of law. University scientific notes. 2012. No. 3 (43). P. 17–24. Pogrybny S. Analogy of law and analogy of law as means of regulating contractual civil relations. Theory and practice of intellectual property. 2010. No. 5. P. 14–21. Regarding the procedure for applying regulatory legal acts in the event of inconsistency between subordinate legislation: Letter of the Ministry of Justice of Ukraine dated January 30, 2009, No. N-35267-18. https://zakon.rada.gov.ua/laws/show/v3526323-09#Text Sinkevych, O., YurovskаV., Komissarova, N., T., O., & Leheza, Y. (2024). Subjects of public authority in matters of combating terrorism: legal regulation, administrative, and criminal aspects. Ius Humani. Law Journal, 13(1), 1–14. https://doi.org/10.31207/ih.v13i1.332 Tylchyk, Vyacheslav. Matselyk, Tetiana. Hryshchuk, Viktor. Lomakina, Olena. Sydor, Markiian. Leheza, Yevhen. 2022. Administrative and legal regulation of public financial activity: Regulación administrativa y legal de la actividad financiera pública. Cuestiones Políticas, 40(72), 573–581. https://doi.org/10.46398/cuestpol.4072.33 Villasmil Espinoza, Jorge; Leheza, Yevhen; Holovii, Liudmyla. 2022. Reflections for the interdisciplinary study of the Russian Federation’s invasion of Ukraine in 2022: Reflexiones para el estudio interdisciplinario de la invasión de Ucrania por parte de la Federación Rusa en 2022. Cuestiones Políticas, 40(73), 16-24. https://doi.org/10.46398/cuestpol.4073.00 Zadyraka, Nataliia. Leheza, Yevhen. Bykovskyi, Mykola. Zheliezniak, Yevhenii. Leheza, Yulia. 2023. Correlation of Legal Concepts of Administrative Procedure and Administrative Liability in the Sphere of Urban Planning. Journal Cita Hukum Indonesian Law Journal. Vol. 11 No. 1, pp. 33–44, DOI: https://doi.org/10.15408/jch.v11i1.31784 Zavalnyuk S.V. General provisions of applying the analogy of law under the current civil legislation. Journal of Civil Studies. 2014. Issue 16. P. 72–74. Zavalnyuk S.V. Peculiarities of applying the analogy of law under the civil legislation of foreign countries. Journal of Civil Studies. 2016. Issue 20. P. 166–170.